QTL mapping for pest and disease host plant resistance in cassava cultivars Kiroba and AR37-80 and coincidence of QTL with introgression regions from Manihot glaziovii - Myburg, Alexander Andrew (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.